A transfiguração da realidade e imaginário poético em A educação pela pedra - Lopes, Carla Cristina Moreira (2017)
The presente work analyses the tensions between the real and the universe of the imaginary in the ficcional laboratory the poetic language of some poems in A educação pela pedra, by João Cabral de Melo Neto. This language, oriented to the conceptions of poetic image that, pullulates in the imaginary when facing the artistic object. The reading of the cabralina work will focus on the study of the metaphoriztion of language to achieve the essence of poetry. In the first chapter, the concept of the imaginary is explored trough readings of some poems of A educação pela pedra. These poems offer not only elements for the interpretation of what poetic language would be, but also for understanding the second margin of poetic language by the bias of the imaginary. In the second chapter, the symbol will be presented as the intensifier of the metaphorization of the generating language of poetic images; the sign is understood as verbal material of the imagistic creation of the real, which gains body as the imaginary opens the door of poetic receptivity and pairs both games; of the image as the nucleus of cabralino’s poetize, on which the poet works in such a way that it becomes a constellation of significant images. The third on a language constructed from a modulated though in the metafhorical universe of the generative signs of symbolic energy. This work seeks to contribute to the study of poetry and literary criticism. Thus, in incorporates the possibility of the poetry of João Cabral de Melo Neto to be seen as a language dialogue between literary criticism, rhetoric and anthropological studies of the imaginary.